간세포암에 대한 간이식 - 전장용(Jang Yeong Jeon); 이승규(Sung Gyu Lee); 이영주(Young Joo Lee); 박광민(Kwang Min Park); 황신(Shin Hwang); 김기훈(Ki Hun Kim); 안철수(Chul Soo Ahn); 주선형(Sun Hyung Joo); 문덕복(Duk Bock Moon); 주종우(Chong Woo Chu); 민병철(Pyung Chul Min) (Annals of surgical treatment and research, 2003)
KCI Citation Count: 0